Benin : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report, 2021)
The COVID-19 pandemic has severely affected Benin. The authorities' early and decisive action has helped stave off the spread of the virus, and a sizeable fiscal response has kept a recession at bay. Nevertheless, the economy has suffered a substantial downgrade in its economic outlook, with growth slowing down from 6.9 percent in 2019 to 2 percent in 2020, against an initial projection of 7 percent before the pandemic. Large financing needs, opened by the authorities' fiscal response to the crisis, have given rise to an urgent balance of payments need.